Behaviour-based/Trend-based malware analysis on the Android Application - Siow, Jing Kai (2017)
Malicious software, as known as malware, has raised an increasing concern over the recent years. This paper outlines the trend and static behaviour of various malware that are commonly found in the android application. Static behaviour of the malicious application can be reverse-engineer into multiple phase. This can be done using various tools that are available in the internet. With understanding of the smali and Java programming language, the static behaviour of any Android application can be learned easily. Trend analysis can be carried out using the dataset that are gathered throughout various android market, such as wangyi, googleplay, QQ etc. This paper also outlines the techniques and aspects that are used in analysing the trends and the behaviour of the malicious application. Using various analysing aspects and techniques, several statistics data was inferred from the database. These results can be useful for more future study and statistical analysis. This information can be valuable to the community of the malware researchers.